Juridical Analysis of Land Registration Certificate as an Absolute Requirement in the Mortgage Execution Auction - Alimah, Adine (Universitas Negeri Semarang, 2024)
Abstract SKPT is a document that is a mandatory requirement in an auction application. The SKPT must be submitted by the creditor to the KPKNL when requesting an auction. However, many auctions were canceled by the KPKNL Office due to the lack of complete SKPT requirements which were not fulfilled by the creditors. This research aims to find out the regulations and urgency of the SKPT document as a condition for holding an auction. The research method used in this research is a normative juridical method through statutory and conceptual approaches. The data source used in this research is secondary data through reviewing legal regulations, books, journals, articles and other sources. In this research, it was found that there are still many creditors who do not know that the SKPT document is a mandatory requirement in carrying out auctions. The government should be able to provide outreach regarding the importance of the SKPT document as a condition for holding auctions for the execution of mortgage rights. Keywords: SKPT, Auction Implementation, Auction Canceled.